2006
DOI: 10.1002/ab.20137
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to maternal vs. paternal partner violence, PTSD, and aggression in adolescent girls and boys

Abstract: Adolescents who witness interparental violence (IPV) are at increased risk for perpetrating aggressive acts. They are also at risk for post-traumatic stress disorder (PTSD). In this study, we examined the relation between exposure to maternal vs. paternal physical IPV and adolescent girls' and boys' aggressive behavior toward mothers, fathers, friends, and romantic partners. We also assessed the influence of PTSD (as assessed by the Diagnostic Interview for Children and Adolescents-IV (DICA-IV)) on the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
103
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 32 publications
16
103
1
2
Order By: Relevance
“…We also extended the findings of Lindgren and colleagues (2012), as we included a measure of psychological distress to directly show the pathway from trauma to increased distress to coping expectancies to in- Furthermore, we demonstrated that the findings on childhood trauma could generalize to a sample of children who grew up in homes with parental violence and to a sample that included males. This is not surprising because children who are exposed to parental violence experience similar long-term effects as children who experience other traumas, including increased levels of PTSD, dysregulated affect, earlier initiation of drinking, and increased likelihood of substance use disorders (Caetano et al, 2003;Moretti et al, 2006;Wood & Sommers, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also extended the findings of Lindgren and colleagues (2012), as we included a measure of psychological distress to directly show the pathway from trauma to increased distress to coping expectancies to in- Furthermore, we demonstrated that the findings on childhood trauma could generalize to a sample of children who grew up in homes with parental violence and to a sample that included males. This is not surprising because children who are exposed to parental violence experience similar long-term effects as children who experience other traumas, including increased levels of PTSD, dysregulated affect, earlier initiation of drinking, and increased likelihood of substance use disorders (Caetano et al, 2003;Moretti et al, 2006;Wood & Sommers, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Children exposed to violence between their parents suffer similar long-term effects as do children who experience other traumas, including increased levels of PTSD, internalizing and externalizing problems, and increased likelihood of substance use disorders (Caetano et al, 2003;GrahamBermann & Perkins, 2010;Moretti et al, 2006;Wood & Sommers, 2011). Hamburger and colleagues (2008) assessed the history of child maltreatment in 3,559 students between grades 7 and 12 in a high-risk community.…”
mentioning
confidence: 99%
“…Moretti, Obsuth, Odgers, and Reebye (2006) explored the relationship between exposures to IPV aggressive behavior in adolescents by including posttraumatic stress disorder (PTSD) as an important factor in the dynamics involved. Specifically, the researchers theorized that adolescents with PTSD would be more predisposed toward relationship violence.…”
Section: Factors Influencing Ipv and The Igtv Among Hispanic Young Admentioning
confidence: 99%
“…The overwhelming majority of participants (i.e., 89% of the girls and 92% of the boys) resided in two-parent families (Moretti et al, 2006). Nevertheless, the fact that roughly 10% of the adolescents did not add weight to the assertion that the U.S. data underestimate the number of children exposed to IPV (McDonald, Jouriles, RamisettyMikler, Caetano, & Green, 2006).…”
Section: Factors Influencing Ipv and The Igtv Among Hispanic Young Admentioning
confidence: 99%
See 1 more Smart Citation